Desenvolvimento de métrica de avaliação bilíngue por estrutura frasal aplicada à tradução automática - Silva, Alan Henrique Ferreira (2021)
This work proposes a metric capable of evaluating automatic bilingual translations, through the use of phrasal structures between the source and target languages. Existing methods currently provide a dependent assessment of large amounts of data as texts examples. The proposed methodology uses as a database the association of generic phrasal structures between the source and target language to assess the text quality, resulting given by an automatic translation machine. The method validation is performed using comparative studies between the evaluations generated by the proposed metric and the BLEU and METEOR metrics. The results obtained shows greater accuracy of evaluation of the proposed metric compared to the other metrics, with an improvement of approximately $5%$ compared to the results of the evaluation of human translators. The results obtained in the tests validate the capability of the metric as an auxiliary tool in the evaluation of machine translations.